The Influence Of The Implementation Of Contextual Learning Models On Learning Outcomes In Social Studies Subjects Of Grade IX Students Of SMPN 13 Bengkulu City - Ulfadillah, Tri Muthi Ah; Suharmi , Suharmi; Kalsum, Ummi (Universitas Dehasen Bengkulu, 2025)
This study aims to: (1) determine the contextual learning model in the subject of social studies of class IX students of SMP 13 Bengkulu City (2) determine the learning outcomes in the subject of social studies of class IX students of SMP 13 Bengkulu City, and (3) determine the effect of implementing the contextual learning model on learning outcomes in the subject of social studies of class IX students of SMP 13 Bengkulu City. This type of research is quantitative research by measuring and analyzing the relationship between two variables that can be measured numerically. The data collection techniques used were observation, questionnaires, and documentation. The sample in this study was 60 students with a purposive sampling technique. The data analysis technique used the average (mean) and the f test. The results of the study showed that the contextual learning model of students was in the good category, learning outcomes were in the very good category, and there was a positive and significant influence between the contextual learning model and student learning outcomes. This shows that the better the contextual learning model, the better it is in terms of student learning outcomes.